Influence of physical activity, diet, psychic stress and other diseases on psoriaris - Spozowski, Karol; Powroźniak, Ewelina; Raksa, Karolina; Czarkowski, Marcin; Oleksa, Paulina (Journal of Education, Health and Sport, 2022)
Introduction and objective: Psoriasis is a chronic inflammatory skin disease characterized by improperly differentiating epidermal keratinocytes. It may be associated with many coexisting diseases, mainly of the digestive, circulatory and autoimmune systems. Materials and methods: Pubmed database was searched. The criteria for qualifying the articl for the review were the following keywords: psoriasis, diet, sport, exercises, stress. 20 articles from 2017 to 2022 were analyzed. Description of the state of knowledge: Psoriasis has many links with metabolism, which depends on diet, exercise, and other diseases in the body. The excessive amount of pro-inflammatory substances can be regulated by supplying the body with anti-inflammatory ingredients in the diet as well as by physical activity that reduces the level of visceral fat. Many other diseases related to, inter alia, inflammation of the intestines or the state of the intestinal microbiota also affect the systemic distribution of cytokines and adipokines. An important factor influencing health is also mental stress and even epigenetic factors. Summary: Increased physical activity helps fight the main consequences of psoriasis. A similar effect is demonstrated by a low-calorie diet with a high content of anti-inflammatory ingredients and antioxidants and avoidance of pro-inflammatory substances. Treating other comorbidities and maintaining a low level of mental stress also have a positive effect on patients with psoriasis. All of the above interventions are effective complementary to pharmacological therapy.